2008
DOI: 10.1016/j.devcel.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The TEAD/TEF Family Protein Scalloped Mediates Transcriptional Output of the Hippo Growth-Regulatory Pathway

Abstract: The Hippo (Hpo) kinase cascade restricts tissue growth by inactivating the transcriptional coactivator Yorkie (Yki), which regulates the expression of target genes such as the cell death inhibitor diap1 by unknown mechanisms. Here we identify the TEAD/TEF family protein Scalloped (Sd) as a DNA-binding transcription factor that partners with Yki to mediate the transcriptional output of the Hpo growth-regulatory pathway. The diap1 (th) locus harbors a minimal Sd-binding Hpo Responsive Element (HRE) that mediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
637
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(656 citation statements)
references
References 47 publications
19
637
0
Order By: Relevance
“…Subsequent biochemical studies showed that Wts directly phosphorylates and inhibits Yki (Dong et al, 2007). Scalloped (Sd), the homolog of mammalian TEAD family transcription factors, were found to be critical partners of Yki in the regulation of gene expression (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008;Zhao et al, 2008;Zhang et al, 2009a). Several transcriptional targets of the Hippo pathway have been identified, including cyclin E, which directly promotes cell cycle progression and cell proliferation, and diap1, which inhibits apoptosis (Tapon et al, 2002;Jia et al, 2003;Udan et al, 2003;Wu et al, 2003;Lai et al, 2005).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent biochemical studies showed that Wts directly phosphorylates and inhibits Yki (Dong et al, 2007). Scalloped (Sd), the homolog of mammalian TEAD family transcription factors, were found to be critical partners of Yki in the regulation of gene expression (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008;Zhao et al, 2008;Zhang et al, 2009a). Several transcriptional targets of the Hippo pathway have been identified, including cyclin E, which directly promotes cell cycle progression and cell proliferation, and diap1, which inhibits apoptosis (Tapon et al, 2002;Jia et al, 2003;Udan et al, 2003;Wu et al, 2003;Lai et al, 2005).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…The TEAD family transcription factors were identified to be critical partners of YAP and TAZ in the regulation of gene expression (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008;Zhao et al, 2008;Zhang et al, 2009a). Disruption of YAP-TEAD interaction abolishes YAP-dependent gene transcription and largely diminishes YAP-induced cell proliferation, oncogenic transformation, and epithelial-to-mesenchymal transition (EMT) .…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 99%
“…The phosphorylation of Yki by Wts inhibits Yki nuclear localization, preventing it from acting on its growth-promoting and apoptosisinhibiting targets. Yorkie functions with the transcription factor Scalloped in the regulation of growth control [58][59][60] .…”
Section: Growth Control By Fat Pcp Regulatorsmentioning
confidence: 99%
“…These proteins suppress growth by the phosphorylation or cytosolic retention of the transcriptional coactivator Yorkie (Yki), which cannot bind to DNA directly (Huang et al, 2005). Yki interacts with a transcription factor Scalloped (Sd), which induces tissue overgrowth (Goulev et al, 2008;Wu et al, 2008;Zhang et al, 2008). The Wts-Hpo signaling factors are now considered as general regulators of organ size in both Drosophila and mammals (Reddy and Irvine, 2008;Halder and Johnson, 2010;Pan, 2010;Zhao et al, 2010).…”
Section: Fig 2 Drosophila Adult Leg Phenotypes Ofmentioning
confidence: 99%